On Chebyshev Polynomials and Torus Knots - Gavrilik, A.M.; Pavlyuk, A.M. (Відділення фізики і астрономії НАН України, 2010)
In this work, we demonstrate that the q-numbers and their two-parameter generalization, the q,p -numbers, can be used to obtain some polynomial invariants for torus knots and links. First, we show that the q-numbers, which are closely connected with the Chebyshev polynomials, can also be related with the Alexander polynomials for the class T(s, 2) of torus knots, s being an odd integer, and used for finding the corresponding skein relation. Then, we develop this procedure in order to obtain, with the help of q, p - numbers, the generalized two-variable Alexander polynomials and to prove their direct connection with the HOMFLY polynomials and the skein relation of the latter. У роботi показано, що q-числа та їх двопараметричнi узагальнення, q, p-числа можна використати для отримання деяких полiномiальних iнварiантiв торичних вузлiв i зачеплень. По-перше, показано, що q-числа, якi тiсно пов’язанi з полiномами Чебишова, можуть бути пов’язанi з полiномами Александера для класу T(s, 2) торичних вузлiв, де s – непарне цiле число, i використанi для знаходження вiдповiдного скейн-спiввiдношення. Потiм використано цю процедуру для отримання за допомогою q, p-чисел, двопараметричних узагальнених полiномiв Александера та показано зв’язок останнiх iз полiномiальними iнварiантами HOMFLY та їх скейн-спiввiдношенням.